Pengoptimalan E-Government Di Indonesia Berdasarkan Prinsip-Prinsip Good Government - Asna Rohmatun Nur Azizah; Fatma Ulfatun Najicha (Faculty of Law, Diponegoro University, 2022)
The purpose of this research is to know the development of e-government in Indonesia and to know how to optimize e-government. The research method used is descriptive research conducted with a qualitative approach. This study aims to describe, analyze and interpret the implementation of E-Governmant in government public services. The results obtained from this study are that one way to achieve a country that has a good governance system is to apply e-government as a public service. However, its application in the field in Indonesia has not been so optimal. Therefore, to optimize e-government its application can be based on the principles of good governance in addition to relying on Presidential Instruction No. 3 of 2003. Keywords: e-government, goverment, good government Abstrak Tujuan dari penelitian ini adalah mengetahui perkembangan e-government di Indonesia dan mengetahui cara pengoptimalan e-governtment. Metode penelitian yang digunakan adalah penelitian deskriptif yang dilakukan dengan pendekatan kualitatif. Penelitian ini bertujuan untuk mendeskripsikan, menganalisis dan menginterpretasikan mengenai implementasi E-Governmant dalam pelayanan publik pemerintah. Hasil yang didapat dari penelitian ini adalah Salah satu cara untuk mencapai negara yang memiliki sistem pemerintahan yang baik (good governance) adalah dengan menerapkn e-government sebagai pelayanan publiknya. Namun, penerapannya di lapangan pada negara Indonesia belum begitu optimal. Oleh karena itu, untuk mengoptimalkan e-government penerapannya dapat berpatokan pada prinsip-prinsip good governance selain berpatokann pada Inpres No. 3 tahun 2003.